The Behaviour of Contaflex Soft Contact Lens Material During Hydration - Joseph Towler; Markus Zaplachinski; Roberto Montiel; Nikhil Murari; Christine Deng; Rimmo Lego; Arwa Fathy; Ahmed Abass (Gels)
The aim of this study was to quantitatively evaluate the swelling and transparency behaviour of Contaflex soft contact lens materials with varying water-content (38–77%) using high-resolution digital imaging and infrared LiDAR. Contaflex materials with 38%, 55%, 58%, 67% and 77% nominal water-contents, denoted as C38, C55, C58, C67, and C77, were tested. Hydrogel samples (N = 5 per group) were monitored over 24 h in pH 7.1 phosphate-buffered saline. Dimensional changes were assessed via linear and radial expansion factors (LEF and REF), and transparency was tracked during hydration. All groups exhibited rapid initial swelling followed by continued expansion. LEF and REF values increased with water-content; C77 reached LEF and REF values of 1.563 ± 0.093 and 1.536 ± 0.052, while C38 stabilised near 1.201 ± 0.019 and 1.179 ± 0.011, respectively. Refractive index decreased with hydration, from 1.552 in C38 to 1.372 in C77. Power simulations revealed deviations beyond ISO tolerance limits in most materials, particularly those with higher water-content. Transparency changes were consistent with swelling dynamics. These findings support the need for material-specific design adjustments to account for hydration-related dimensional and optical changes in soft contact lenses.